2010
DOI: 10.1088/0031-9155/55/7/009
|View full text |Cite
|
Sign up to set email alerts
|

Transport-based quantitative photoacoustic tomography: simulations and experiments

Abstract: In this paper we describe a method for quantitative photoacoustic tomography (qPAT) based on the photon radiative transfer equation (RTE) coupled with the Helmholtz photoacoustic wave equation. Considerable simulations and tissue-like phantom experiments are conducted to evaluate transport-based qPAT in comparison with diffusion-based qPAT. In these comparative simulations and experiments, we systematically examine the effects of the ratio of mu(a)/mu'(s) (absorption/reduced scattering coefficient), the anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…30,32 To overcome this problem, one approach has been to assume the scattering as known and to estimate only the absorption. [35][36][37][38][39][40] This, however, is unrealistic since in practical applications scattering is usually not exactly known. This approach has been improved by modeling the errors caused by the fixed scattering assumption by using a Bayesian approximation error modeling.…”
Section: Introductionmentioning
confidence: 99%
“…30,32 To overcome this problem, one approach has been to assume the scattering as known and to estimate only the absorption. [35][36][37][38][39][40] This, however, is unrealistic since in practical applications scattering is usually not exactly known. This approach has been improved by modeling the errors caused by the fixed scattering assumption by using a Bayesian approximation error modeling.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that U calculated with PDE became larger than that with MC simulation as l a increased. The difference between PDE and RTE was demonstrated in the 2D medium in the literature [30]. It is said that the photon flux calculated with 2D PDE was smaller than that with 2D RTE in the target region with a large absorption coefficient.…”
Section: Effects Of the Approximations On The Absorbed Light Energymentioning
confidence: 90%
“…Additionally, it is not appropriate to use PDE when the absorption coefficient is not sufficiently smaller than the scattering coefficient. Yao and coworkers demonstrated that the RTE-based image reconstruction was more accurate than the PDE-based image reconstruction in a 2D medium when PDE was invalid because of the large absorption coefficient and the anisotropy of the light scattering [30]. However, the effects of the approximations of light propagation on QPAT have not been investigated quantitatively and systematically.…”
Section: Introductionmentioning
confidence: 99%
“…The phantom is composed of 1% Intralipid R (Sigma Aldrich, St. Louis, MO, USA), 1% highly purified agar (A0930-05, USBiological, Swampscott, MA, USA), and deionized water. Intralipid R is a phospholipid emulsion that is widely used for optical and photoacoustic phantom studies, because it is a homogeneous and turbid medium without distinct absorption bands [11,13,17,30,59]. Agar was used to solidify the phantom, without notably increasing turbidity or absorption [11].…”
Section: Methodsmentioning
confidence: 99%